Pressure-induced enhancement and retainability of optoelectronic properties of NiPS3 - Sixue Fang; Quanjun Li; Zonglun Li; Qing Dong; Xiaoling Jing; Chenyi Li; Haiyan Li; Bo Liu; Ran Liu; Bingbing Liu (Materials Research Letters, 2023)
Here, we report significant pressure-modulate optoelectronic properties of NiPS3. Upon compression, NiPS3 exhibited a photocurrent increase of five orders of magnitude over the initial value. Interestingly, when NiPS3 was finally decompressed to ambient conditions, the photocurrent could maintain a two-order-of-magnitude enhancement. In addition, the spectral response range was extended to the near-infrared spectral range (up to 1650 nm) under high pressure. Raman and XRD measurements and theoretical calculations revealed significant enhancement in both interlayer and intralayer interactions during compression, leading to a remarkable modulation of the optoelectronic properties.